Ecological and geochemical assessment of the soil in Perm - Shishkin, M.A.; Gusev, V.A.; Sherstobitova, N.P. (Perm Federal Research Centre Journal, 2020)
Based on the results of environmental and analytical studies, the level of chemical pollution of urban soils with trace elements of 1, 2, and 3 hazard classes and organic toxicants was assessed. Spatial mapping of ecological condition of the residential zone soils in Perm was performed, the allocation of anomalous sites being indicated.